2015
DOI: 10.5194/hess-19-4201-2015
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal change in streamflow associated with anthropogenic disturbances in the tropical Andes

Abstract: Abstract. Andean headwater catchments are an important source of freshwater for downstream water users. However, few long-term studies exist on the relative importance of climate change and direct anthropogenic perturbations on flow regimes in these catchments. In this paper, we assess change in streamflow based on long time series of hydrometeorological data and land cover reconstructions in the Pangor catchment (282 km 2 ) located in the tropical Andes. Three main land cover change trajectories can be dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 54 publications
1
28
0
10
Order By: Relevance
“…February to April is the most humid period with a monthly precipitation of slightly more than 100 mm, while July and August is the dry season with a monthly precipitation of about 35 mm. In addition to the rainfall, there is a continuous moisture input from clouds and fog in this high‐altitude páramo ecosystem (Molina et al, ). The mean annual air temperature is 8 °C with little seasonal variation.…”
Section: Páramo Ecosystemmentioning
confidence: 99%
“…February to April is the most humid period with a monthly precipitation of slightly more than 100 mm, while July and August is the dry season with a monthly precipitation of about 35 mm. In addition to the rainfall, there is a continuous moisture input from clouds and fog in this high‐altitude páramo ecosystem (Molina et al, ). The mean annual air temperature is 8 °C with little seasonal variation.…”
Section: Páramo Ecosystemmentioning
confidence: 99%
“…But diurnal temperature cycles are highly marked and can range between 0 and 20 °C (Buytaert et al, , ; Córdova et al, ). Luteyn (); Buytaert et al () and Molina et al () have reported annual precipitation amounts between 500 and 3000 mm year −1 , with an exceptionally high spatiotemporal variability (Buytaert et al, ; Célleri et al, ). In contrast, characterizing reference evapotranspiration has been limited by the scarce availability of meteorological data.…”
Section: Introductionmentioning
confidence: 99%
“…This is somehow surprising as research on the land use and land cover patterns effect on runoff is well documented at catchment (Chaves et al . , ; Coe, Latrubesse, Ferreira, & Amsler, ; Molina, Vanacker, Brisson, Mora, & Balthazar, ; Neill et al . , ; Ochoa‐Tocachi et al .…”
Section: Discussionmentioning
confidence: 99%
“…, ; Iñiguez–Armijos, Leiva, Frede, Hampel, & Breuer, ; Molina et al . , ; Ochoa‐Tocachi et al . , ; Tapia‐Armijos, Homeier, Espinosa, Leuschner, & de la Cruz, ), man‐made changes in natural land cover and land use have been identified as an emerging ecological problem.…”
Section: Discussionmentioning
confidence: 99%